PENGARUH PENERAPAN MODEL PROBLEMBASED LEARNING DAN MINAT BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI IPS SMA NEGERI 8 PADANG - Febri Herlina (Jurnal Ecogen, 2018)
The research was conducted in eaght high school XI Padang. The purpose of this study is to disclose : (1) Difference learning outcomes of students who are taught by problem based learning model with learning outcomes of students who were taught by conventional model on economic subjects,(2). Difference learning outcomes of students who have high interest to learn the learning outcomes of students who have low interest to learn on economic subjects,(3). The interaction between teaching models and learning interest in influencing stuent learning outcomes on economic subjects.This research uses quasi experimental approach with 2x2 factorial design. The study population is students who are studying in class XI semesters 2017-2018 of 4 classes. The samples taken by selecting two classes that have an average value of the same/near same (purposive sampling techniques). Furthermore, from the selection of two classes were randomly selected to determine the control class and experimental class.the selected experimental class is a class XI 3 by the number of students 32 students, and the control class is the class is the class of XI 2 selected by number of 32 students. Learning outcomes data are collected through study and test results were analyzed with analysis of variant (ANOVA). Based on the results of research found that (1). The average learning outcomes of students who are taught using the problem based learning model is higher than the learning outcomes of students taught with conventional models on economic subjects,(2). Average students learning outcomes that have a higt interest to study higher than students who have low interest on economic subjects (3). There is on interaction between teaching models and studentsinterestin influencing student learning outcomes on economic subjects in high school 8 padang.Keyword:Problem Based Learning Models, interest to learn, and learning outcomes